Zika virus infection suppresses CYP24A1 and CAMP expression in human monocytes (2024)
ABSTRACT: Monocytes are the primary targets of Zika virus (ZIKV) and are associated with ZIKV pathogenesis. Currently, there is no efective treatment for ZIKV infection. It is known that 1,25-dihydroxy vitamin D3 (VitD3) has strong antiviral activity in dengue virus-infected macrophages, but it is unknown whether VitD3 inhibits ZIKV infection in monocytes. We investigated the relationship between ZIKV infection and the expression of genes of the VitD3 pathway, as well as the infammatory response of infected monocytes in vitro. ZIKV replication was evaluated using a plaque assay, and VitD3 pathway gene expression was analyzed by RT-qPCR. Pro-infammatory cytokines/chemokines were quantifed using ELISA. We found that VitD3 did not suppress ZIKV replication. The results showed a signifcant decrease in the expression of vitamin D3 receptor (VDR), cytochrome P450 family 24 subfamily A member 1 (CYP24A1), and cathelicidin antimicrobial peptide (CAMP) genes upon ZIKV infection. Treatment with VitD3 was unable to down-modulate production of pro-infammatory cytokines, except TNF-α, and chemokines. This suggests that ZIKV infection inhibits the expression of VitD3 pathway genes, thereby preventing VitD3-dependent inhibition of viral replication and the infammatory response. This is the frst study to examine the efects of VitD3 in the context of ZIKV infection, and it has important implications for the role of VitD3 in the control of viral replication and infammatory responses during monocyte infection